THE TOTAL LEUKOCYTE COUNT OF ELDERLY PATIENTS CONFIRMED COVID-19 WITH/WITHOUT A VENTILATOR IN A SURABAYA GENERAL HOSPITAL IN 2021 - Fitriani, Safira Indah; Handayani, Nur Septia; Widyastuti, Erlinda; Kurniati, Anita (Journal of Vocational Health Studies, 2023)
Background: Coronavirus is a virus that attacks the immune system, especially the human respiratory system. The elderly are at high risk of being infected with Coronavirus Disease-19 (COVID-19), and as they get older, they are at risk of experiencing severe symptoms when infected with COVID-19. Leukocytes play a role in the immune system against foreign objects. The leukocyte count will decrease in the elderly. On the other hand, the increase of leukocytes plays a role as a clinical sign that is useful to be a predictor of body immunity when infected with COVID-19. Purpose: To determine the total leukocyte count in elderly patients that were confirmed COVID-19 and hospitalized with and without a ventilator. Method: This study was a cross-sectional design study involving 93 elderly patients in General Hospital Surabaya. Result: The results showed no difference in the total leukocyte count in elderly hospitalized patients with and without a ventilator (p-value = 0.756). Age above 70 years old increases the risk of patients requiring a ventilator up to 1.7 times compared to patients under 70 years old. The highest leukocyte count was 20.880/mm3, and the lowest was 3.760/mm3. The ratio of leukocyte count in elderly patients with a ventilator group is 1 : 3 for low and high leukocyte counts, respectively. Conclusion: Leukocyte count is an important parameter as the predictor of the progression of the disease and helps in the decision regarding treatment strategy to prevent the cytokine storm.